2006
DOI: 10.1051/0004-6361:20065433
|View full text |Cite
|
Sign up to set email alerts
|

The new nebula in LDN 1415 – A cry from the cradle of a low-luminosity source

Abstract: Aims.A survey for candidate Herbig-Haro objects was performed to search for evidence of star formation in Galactic dark clouds Methods. For this aim true colour images were created from blue, red, and infrared DSS2 plates and inspected. Follow-up I-band, Hα, and [S ii] CCD imaging as well as long-slit spectroscopy using the Tautenburg 2-m telescope was carried out to verify candidate objects.Results. In the case of LDN 1415, the presence of a Herbig-Haro flow could be revealed which is henceforth named HH 892.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
(39 reference statements)
2
26
0
Order By: Relevance
“…The spectrum of HH 892A resembles to that of a high excitation HHO (Raga & Canto, 1996). An active Herbig-Haro flow towards L1415 has also been reported by Stecklum et al (2007) based on the longslit spectroscopic study. On the DSS image of L1415, a HHO candidate near IRAS 04376+5413 was detected (Stecklum et al, 2007).…”
Section: L1415supporting
confidence: 58%
See 2 more Smart Citations
“…The spectrum of HH 892A resembles to that of a high excitation HHO (Raga & Canto, 1996). An active Herbig-Haro flow towards L1415 has also been reported by Stecklum et al (2007) based on the longslit spectroscopic study. On the DSS image of L1415, a HHO candidate near IRAS 04376+5413 was detected (Stecklum et al, 2007).…”
Section: L1415supporting
confidence: 58%
“…An active Herbig-Haro flow towards L1415 has also been reported by Stecklum et al (2007) based on the longslit spectroscopic study. On the DSS image of L1415, a HHO candidate near IRAS 04376+5413 was detected (Stecklum et al, 2007). Using subsequent Hα and [SII] imaging, Stecklum et al (2007) confirmed the presence of the emission line object with no counterpart.…”
Section: L1415mentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast to the previous results, a Chandra observation was unable to detect the outburst source that illuminates the new nebula associated with IRAS 04376+5413 in LDN 1415, located at d ∼ 170 pc (Kastner et al 2006a;Stecklum 2006;Stecklum et al 2007).…”
Section: Introductionmentioning
confidence: 59%
“…Thus we conclude that this object, Fig. 4 SED of the candidate proto-brown dwarf (Stecklum et al 2007). The line displays the SED of L1014-IRS (Young et al 2004) for comparison BHR111-IR, is likely driving the outflow.…”
Section: Bhr111-a Starless Core Remains Starless?mentioning
confidence: 79%